Assessing self reported ,organizational citizenship behaviour: the role of organizational climate and leadership styles. (2011)
The study assessed the role of organizational climate and leadership styles in predicting organizational citizenship behaviour-of both private and public sectors employees. A total of 203 employees made up of 128 (63.1911 public sector employees and 75 (36.9%) private sector employees were sampled in a cross-sectional survey. Male participants were 129 (63.5%) with74 (36.5%) females. A structured questionnaire made up of' three validated scales was used in data collection. Multiple regression analysis and t-test of independent means were used in analysing the data. Results showed that organizational climate significantly predict organizational citizenship behavior, while leadership styles did not. Also, age of the employees had a significant influence on OCB. This implies that human resource management should look beyond having a good leadership style, because this occupies a little position as far as organizational climate is concerned. Organizations should also strive to enhance the welfare of their employees in order to retain their employees since age is significantly important in predicting OCB.